Aspek Hukum Pemanfaatan Barang Milik Negara Perwakilan Republik Indonesia di Luar Negeri - Pratidina, Khania Nirmala (Lex Prospicit, 2025)
The utilization of State Property owned by ministries/institutions is not a new thing in the national asset management system, but in its development, a problem was found that there are State Properties owned by Representatives of the Republic of Indonesia abroad that have not been utilized optimally in matters outside their duties and functions to support diplomatic activities abroad. This research is a normative juridical research that focuses on literature study regarding the regulation of the use of state property by Representatives of Foreign Countries in international law provisions and how Indonesian national law provisions regulate the utilization of State Properties owned by Representatives of the Republic of Indonesia abroad for commercial activities. Based on the research, it can be concluded that the utilization of State Properties owned by Representatives of Foreign Countries for commercial activities is contrary to international law, especially the Vienna Convention on Diplomatic Relations 1961 and the Vienna Convention on Consular Relations 1963. However, there are exceptions that provide space for Representatives of Foreign Countries, namely if of course with the consequence that the State Properties releases its privileges such as immunity and tax exemption. In national legal provisions, the management of State Properties abroad is regulated in Minister of Finance Regulation Number 271/PMK.06/2015 and Minister of Foreign Affairs Regulation Number 5 of 2016, but both regulations have not accommodated the use of State Properties for Representatives of the Republic of Indonesia abroad. Bahasa Indonesia Abstrak: Pemanfaatan Barang Milik Negara (BMN) yang dimiliki oleh kementerian/lembaga bukan merupakan hal baru dalam sistem tata kelola aset nasional, namun pada perkembangannya ditemukan permasalahan bahwa terdapat BMN yang dimiliki oleh Perwakilan Republik Indonesia di luar negeri yang belum dimanfaatkan secara maksimal dalam hal di luar tugas dan fungsinya mendukung kegiatan diplomasi di luar negeri. Penelitian ini adalah penelitian yuridis normatif yang berpusat pada studi kepustakaan mengenai pengaturan penggunaan BMN oleh Perwakilan Negara Asing dalam ketentuan hukum internasional serta bagaimana ketentuan hukum nasional Indonesia mengatur mengenai pemanfaatan BMN yang dimiliki oleh Perwakilan Republik Indonesia di luar negeri untuk kegiatan yang bersifat komersial. Berdasarkan penelitian dapat disimpulkan bahwa pemanfaatan BMN milik Perwakilan Negara Asing untuk kegiatan komersial merupakan hal yang bertentangan dengan hukum internasional khususnya Vienna Convention on Diplomatic Relation 1961 dan Vienna Convention on Consular Relation 1963. Namun terdapat pengecualian yang memberikan ruang kepada Perwakilan Negara Asing, yaitu apabila tentunya dengan konsekuensi bahwa BMN tersebut melepaskan privileges yang dimiliki seperti imunitas dan pembebasan pajak. Dalam ketentuan hukum nasional, pengelolaan BMN di luar negeri diatur dalam Peraturan Menteri Keuangan Nomor 271/PMK.06/2015 dan Peraturan Menteri Luar Negeri Nomor 5 Tahun 2016, namun kedua peraturan tersebut belum mengakomodir pemanfaatan BMN bagi Perwakilan Republik Indonesia di luar negeri.